Pengaruh Pembelajaran Daring Terhadap Minat Belajar Siswa/i Kelas VIII SMP Negeri 1 Telukdalam - Hia, Niscaya; Gulo, Tridesman Jaya (Metta : Jurnal Ilmu Multidisiplin, 2021)
Online learning is learning that takes place in a network where teachers and those being taught do not meet face-to-face. One of the schools that conduct online learning is SMP Negeri 1 Telukdalam. Like other schools, they carry out teaching and learning activities with online learning. Based on the results of an initial survey conducted by researchers in SMP Negeri 1 Telukdalam there are some students who state that there are many obstacles when online learning takes place. In this study, the aim is to find out how the influence of online learning on students interest in class VIII SMP Negeri 1 Telukdalam. The type of research used is quantitative with aplication assistance tools SPSS Vers. 16. Based on the results of the study showed that the relationship between the variable X with the variable Y of 0,857 indicates the rxy correlations that occurs between the independent variable and the dependet variable is in a “Very Strong” relationship. (0,80-1,000). Obtained a coefficient of determination () of 0,735 so that it can be shown that the diversity of the depedent variable (interest in learning) can be influenced by the independent variable (online learning). The value of tcount (13,308) > ttable (1.668) and a significant level of 0,000 < 0.05, then the decision is Ha accepted and H0 is rejected with the meaning that the online learning variable has a positive and significant effect on the variable interest in student learning in class VIII SMP Negeri 1 Telukdalam.